Exploring Thermomyces lanuginosus Lipase (TLL)-PdNPs Nanohybrid as Suitable Catalyst for One-pot Synthesis of Bis(3-indolyl)phenylmethane - Santos, A. Sofia (2024)
This work was supported by the Spanish Government, the Spanish National Research Council (CSIC). project PTDC/QUI‐QOR/0712/2020. We also thank Dr. Martinez from Novozymes. We acknowledge support of the publication fee by the CSIC Open Access Publication Support Initiative through its Unit of Information Resources for Research (URICI) Publisher Copyright: © 2023 The Authors. ChemCatChem published by Wiley-VCH GmbH.